University Retirement Community at Davis: A Combined Heat and Power Case Study - Damberger, Thomas (Distributed Generation & Alternative Energy Journal, 2005)
Electricity is like any other commodity, it is subject to the laws of supply and demand. If the demand increases; prices trend upward. If the supply component cannot increase to meet the new level of demand, a pressure to increase price is a nominal reaction to market forces. This is epitomized in what we experienced early in 2004 with the normally ubiquitous gasoline commodity. When electricity prices quadrupled over the course of a few months, many were unprepared. The unprepared directly experienced a lack of commodity, while others planned ahead with a diversified energy portfolio mitigating these risks. Because prices of electricity are highly volatile and will probably rise again, companies can use economic sense by incorporating certain technologies to better prepare their operation to manage energy costs—even during blackouts. Because of the operational nature of hospitals and retirement facili- ties, which operate 7/24, there are options to help reduce the cost of those operations. There are early market adopters of certain energy tech- nologies who demand a high level of reliability and power quality 7/24 from their central plants. Telco-hotels and server farms are one such industry that requires this level of reliability and quality. These same technologies can also be adapted for hospitals and retirement facilities. And why not, when it comes to a human life hanging in balance based on the reliability of the utility grid or emergency generator? Any finan- cial incentives or savings achieved are simply a secondary benefit when considering the reliability of the electricity commodity. University Retire-ment Community at Davis decided it was time to take control of their energy future, thereby assuring a diversified, cost-effective, and reliable energy portfolio by adapting one of these technologies for their tenants.